Determinants Factors of Crafters Performance of SME’s at Tapis, Province of Lampung - Mieke Rahayu; Betty Magdalena (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2021)
This study aims to analyze and prove empirically the influence of managerial ability, work culture, organizational characteristics both partially and simultaneously on the innovation capability and performance of crafters at Tapis SMEs in Lampung Province. The research methods in this research are descriptive and verification methods. The population was 1,302 Tapis crafter in Lampung Province and a sample of 305 and as owner crafters as respondents, with questionnaires as data collection techniques, and data analysis technique was Structural Equation Modeling (SEM), using Lisrel 8.70. The results showed that partially or simultaneously, managerial ability, work culture, and organizational characteristics had a positive and significant influence on the capability of innovation. The results of this study also showed a positive effect of managerial ability, work culture, and innovation capabilities on the performance of crafters at Tapis SMEs in Lampung Province. Innovation capability can act as an intervening variable that strengthens the influence of managerial ability, organizational culture, and organizational characteristics on the performance of crafters the most dominant work culture influences the performance of craftsmen is 0.356.